Corrigendum Compounds Errors and Again Fails to Support the Specificity of Acupoint Tapping. Issue 2 (February 2022) - Spielmans, Glen I.; Rosen, Gerald M.
Abstract : Abstract: In a prior article (Spielmans, Rosen, Spence-Sing J Nerv Ment Dis 208:628–631, 2020), we demonstrated that Church, Stapleton, Yang, and Gallo's ( J Nerv Ment Dis 206:783–793, 2018) meta-analytic finding that acupoint tapping had specific therapeutic benefit was highly flawed, both statistically and methodologically. Our analysis based on corrected effect sizes found no significant benefit for acupoint tapping at study endpoint. Church, Stapleton, Kip, and Gallo ( J Nerv Ment Dis 208:632–635, 2020) issued a corrigendum in which they reported a new post hoc analysis using follow-up (rather than study endpoint) measures. Shifting to a post hoc outcome while pooling highly disparate follow-up endpoints is problematic; it ignored the nonsignificant result of the a priori analysis. Here, we clarify these issues and address Church, Stapleton, Kip, and Gallo's ( J Nerv Ment Dis 208:632–635, 2020) often irrelevant or confusing responses to our methodological concerns. Considering this recent exchange of articles, and absent meaningful correction to the original incorrect findings, we remain concerned that emotional freedom technique proponents will continue to advance unfounded claims regarding the purported benefits of acupoint tapping.